Mitochondria-targeted antioxidant MitoQ ameliorates ischaemia–reperfusion injury in kidney transplantation models. Issue 9 (8th May 2021) - Hamed, M; Logan, A; Gruszczyk, A V; Beach, T E; James, A M; Dare, A J; Barlow, A; Martin, J; Georgakopoulos, N; Gane, A M; Crick, K; Fouto, D; et al.
Abstract: Background: Ischaemia-reperfusion (IR) injury makes a major contribution to graft damage during kidney transplantation. Oxidative damage to mitochondria is an early event in IR injury. Therefore, the uptake, safety, and efficacy of the mitochondria-targeted antioxidant MitoQ were investigated in models of transplant IR injury. Methods: MitoQ uptake by warm and cooled pairs of pig and declined human kidneys was measured when preserved in cold static storage or by hypothermic machine perfusion. Pairs of pigs' kidneys were exposed to defined periods of warm and cold ischaemia, flushed and stored at 4°C with or without MitoQ (50 nmol/l to 250 µmol/l), followed by reperfusion with oxygenated autologous blood in an ex vivo normothermic perfusion (EVNP). Pairs of declined human kidneys were flushed and stored with or without MitoQ (5–100 µmol/l) at 4°C for 6 h and underwent EVNP with ABO group-matched blood. Results: Stable and concentration-dependent uptake of MitoQ was demonstrated for up to 24 h in pig and human kidneys. Total blood flow and urine output were significantly greater in pig kidneys treated with 50 µmol/l MitoQ compared with controls ( P  = 0.006 and P  = 0.007 respectively). In proof-of-concept experiments, blood flow after 1 h of EVNP was significantly greater in human kidneys treated with 50 µmol/l MitoQ than in controls ( P ≤ 0.001). Total urine output was numerically higher in the 50-µmol/l MitoQ group compared with the control, but the difference did not reach statistical significance ( P  = 0.054). Conclusion: Mitochondria-targeted antioxidant MitoQ can be administered to ischaemic kidneys simply and effectively during cold storage, and may improve outcomes after transplantation. Abstract : This study demonstrated that the mitochondria-targeted antioxidant MitoQ can be administered effectively to isolated kidneys and ameliorates ischaemia–reperfusion injury in ex vivo porcine and human models of kidney transplantation.